Efficacy of Deep Friction Massage Cyriax Techniques in Patello Femoral Pain Syndrome or Anterior Knee Pain in Geriatric Patients - Bisht, Rakhi; Sharma, Rahul; Lakhera, Sakshi; Patra, Anirban; Lal, Sohan; Parmar, Nitin; Raj Bist, Binod (Journal of Neonatal Surgery, 2025)
Patella-femoral pain syndrome (PFPS) is common cause of anterior knee pain the purpose of this article is to review knee anatomy and the literature regarding potential risk factors associated with patella- femoral pain syndrome and pre-rehabilitationstrategies.39to40% of patients still experiencing symptoms after a year of followup, recurrence is common.When symptoms continue after six months of conservative therapy and when clear malalignments are found, surgical intervention should be taken into consideration A comprehensive review of knee anatomy will present the relationships of arterial collateralization, innervations, and soft tissue alignment to the possible multifactoral mechanism involved in PFPS, while attempting to advocate future use of different treatments aimed at non-soft tissue causes of PFPS.